Disney’s Hidden Mouse Trap: The Arbitrariness of Arbitration Clauses - Murphy, Joseph (Bellarmine Law Society Review, 2025)
With an increased reliance on technology and a surge in digital agreements, people have become desensitized to the binding nature of the terms to which they consent in everyday online interactions. This was made readily visible in the aftermath of the death of a woman named Kanokporn Tangsuan due to an allergic reaction in Disney Springs and how her widower found himself legally constrained by the Terms of Service of a free Disney+ trial that he had signed up for without second thought. This paper analyzes the case brought forth by Tangsuan’s husband, Jeffrey Piccolo, the scope of arbitration clauses like those utilized by Disney, and how they restrict possible avenues of legal action. It brings into conversation the power imbalance often apparent in such legal clauses, the question of their continued validity on the basis of legal precedent, and why a reexamination of their prevalence in today’s legal landscape is necessary.